2009
DOI: 10.1159/000222508
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Mechanics

Abstract: This review discusses the pathophysiological aspects of sleep-disordered breathing, with focus on upper airway mechanics in obstructive and central sleep apnoea, Cheyne-Stokes respiration and obesity hypoventilation syndrome. These disorders constitute the end points of a spectrum with distinct yet interrelated mechanisms that lead to substantial pathology, i.e. increased upper airway collapsibility, control of breathing instability, increased work of breathing, disturbed ventilatory system mechanics and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 179 publications
(127 reference statements)
3
41
0
5
Order By: Relevance
“…Given the frequent association of central apnoea and chronic heart failure (CHF) [3], the prevalence of CHF and ischaemic heart disease (IHD) has also been studied in CompSAS. However, no consistent findings were reported [6,9,19,31].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the frequent association of central apnoea and chronic heart failure (CHF) [3], the prevalence of CHF and ischaemic heart disease (IHD) has also been studied in CompSAS. However, no consistent findings were reported [6,9,19,31].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…To a lesser extent, central sleep apnoea syndrome (CSAS) can also be present, characterised by a decreased central respiratory drive during sleep, resulting in decreased or absent ventilation and disturbed gas exchange [3]. In OSAS, repetitive collapse of the upper airway takes place, which will finally lead to O 2 desaturation and arousal.…”
Section: Introductionmentioning
confidence: 99%
“…To explore more effective and targeted treatments for OSA, it is important to address the primary anatomical contributors to increased mechanical loads in the retropalatal area (RP). Previous studies have shown that patients with OSA have smaller retropalatal airways, more lateral pharyngeal wall soft tissues and larger parapharyngeal fat pads than controls [4,5,6,7], implying that these anatomical features may be associated with increased airway mechanical loads. However, individuals may have varied upper airway (UA) collapsibility even if they have the same airway size, suggesting that UA mechanical loads cannot be attributed exclusively to narrowed pharyngeal cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, em pacientes com SAOS, o eixo anteroposterior das VAS é maior, enquanto em indivíduos sem SAOS, é maior o eixo transversal ou, ainda, em indivíduos com SAOS, a área seccional na orofaringe se apresenta com aspecto circunferencial (19,45) . Outros possíveis fatores envolvidos na fisiopatogenia desta entidade são, ainda, citados, destacando-se o reflexo de ativação insuficiente dos músculos dilatadores das VAS nos pacientes com SAOS, durante o sono, especialmente no sono REM (46) , e o aumento da tendência colapsante das paredes faríngeas nestes pacientes (9,44) .…”
Section: Fisiopatologia E Tratamentounclassified
“…Mais recentemente, tem sido demonstrado que o colapso da via aérea superior ocorre durante a fase terminal da expiração, precedendo a apneia (46) .…”
Section: Fisiopatologia E Tratamentounclassified